Influence of memorability on revisit intention in welcome back tourism: The mediating role of nostalgia and destination attachment - Lu, Yan; Lai, Ivan Ka Wai; Liu, Xin Yu; Wang, Xin (Frontiers in Psychology, 2022)
“Welcome Back Tourism” is an important marketing strategy to help overseas Tourism destinations quickly recover from the crisis and enhance their core competitiveness. How to translate the memorability of tourists to revisit intention is the core key to open “Welcome Back Tourism.” This study takes local residents in Guangzhou, Shenzhen and Foshan as the research objects, and tries to explore the influence relationship between memorability of a previous travel experience, nostalgia, destination attachment and revisit intention. The results of 291 valid data showed that memorability of a previous travel experience had positive influence on revisit intention; Nostalgia has a positive effect on destination attachment. Nostalgia and destination attachment play a mediating role in the influence of memorability of a previous travel experience on revisit intention. The contributions and management Recommendations of these findings are discussed.